2009
DOI: 10.1364/oe.17.010895
|View full text |Cite
|
Sign up to set email alerts
|

A finite element beam propagation method for simulation of liquid crystal devices

Abstract: An efficient full-vectorial finite element beam propagation method is presented that uses higher order vector elements to calculate the wide angle propagation of an optical field through inhomogeneous, anisotropic optical materials such as liquid crystals. The full dielectric permittivity tensor is considered in solving Maxwell's equations. The wide applicability of the method is illustrated with different examples: the propagation of a laser beam in a uniaxial medium, the tunability of a directional coupler b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…62 As a result, the 2π phase transition is not only continuous because of the finite extent of the elastic deformation, but the flyback region is also elongated due to fringing fields. [63][64][65] The flyback region is the distance over which the 2π phase jump is smeared out. It has been shown that this effect is detrimental for the steering efficiency η at large angles θ .…”
Section: Laser Beam Steeringmentioning
confidence: 99%
“…62 As a result, the 2π phase transition is not only continuous because of the finite extent of the elastic deformation, but the flyback region is also elongated due to fringing fields. [63][64][65] The flyback region is the distance over which the 2π phase jump is smeared out. It has been shown that this effect is detrimental for the steering efficiency η at large angles θ .…”
Section: Laser Beam Steeringmentioning
confidence: 99%
“…As described in, Ref. 27, it is possible to derive a recurrence scheme for the transverse field by eliminating φ z from the second row of Eq. (4) and substituting the result into the first row of this equation.…”
Section: Wide Angle Beam Propagation Algorithmmentioning
confidence: 99%
“…26 Recently, a full-vector wide angle finite element beam propagation method dedicated to the optical analysis of liquid crystal devices has been presented. 27 In this paper, the modesolver and BPM are compared for the optical analysis of liquid crystal waveguides to illustrate the consistency of both methods and to show they are both attractive for modeling and designing LC waveguides. The basic principles of the finite element modesolver and BPM are reviewed in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Second, part of the fringing fields occurs on the pixel boundary, were some of the loss has already been accounted for by the interpixel gap. As the size of the interpixel gap is smaller than the wavelength and the propagation distance within the liquid crystal considerably more, the effect of the interpixel gap cannot be easily accounted for (it can be accounted for by solving the Maxwell equations within the anisotropic liquid crystal and the metal electrodes [21]). Fringing fields do change the shape of the sinc envelope on the output plane, as can be seen from Fig.…”
Section: Fringing Fields and Liquid Crystal Deformationmentioning
confidence: 99%